The social value of a PASI 90 or PASI 100 response in patients with moderate-to-severe plaque psoriasis in Spain - Maravilla-Herrera, Paulina; Merino, María; Alfonso Zamora, Santiago; Balea Filgueiras, Jesús; Carrascosa Carrillo, José Manuel; Delgado Sánchez, Olga; Dolz Sinisterra, Francisco; García-Ruiz, Antonio; Herranz Pinto, Pedro; Manfredi, Antonio; Martínez Olmos, José; Morales de los Ríos Luna, Paloma; et al. (Frontiers in Public Health, 2023)
Introduction Psoriasis is a chronic disease involving the skin, which significantly impacts the quality of life. Disease severity and treatment efficacy (i.e., response) are assessed through the Psoriasis Area and Severity Index (PASI). A PASI 75 response, i.e., an improvement of at least 75% with respect to the baseline PASI score, has traditionally been used as a therapeutic benchmark in clinical trials. Therapeutic advances have made PASI 90 or PASI 100 responses possible in most patients treated with some biologics. A greater response may generate social value beyond clinical outcomes that would benefit both patients and society. Methods A 1-year economic model was applied to estimate the impact of having a PASI 75, PASI 90, or PASI 100 response in four areas of analysis (quality of life, activities of daily living, work productivity, and out-of-pocket expenditures) and the social value of having a PASI 90 or PASI 100 response in comparison with a PASI 75 response. A mixed-methods approach based on the scientific literature, a focus group with patient, and an advisory committee with psoriasis stakeholders was used. The model included three different scenarios: having a PASI 90 vs a PASI 75 response; a PASI 100 vs a PASI 90 response; and a PASI 100 vs a PASI 75 response. A sensitivity analysis was included. Results The annual economic impact per patient with moderate-to-severe plaque psoriasis having a PASI 75 response was estimated at Ł 6,139, mainly related to labour productivity losses and quality of life reductions. Having a PASI 90 or a PASI 100 response would reduce this impact to €3,956 or €1,353, respectively. Accordingly, the social value of having a PASI 90 instead of a PASI 75 response was estimated at €2,183, and €4,786 with a PASI 100 response. Discussion A PASI 90 or PASI 100 response would have a lower economic impact and a greater social value than a PASI 75 response for patients with moderate-to-severe plaque psoriasis.